Feasibility and acceptability of experience sampling among LGBTQ+ young people with self-harmful thoughts and behaviours - Williams, A. J.; Arcelus, Jon; Townsend, Ellen; Michail, Maria (Frontiers in Psychiatry, 2022)
This study was the first to determine whether it was feasible and acceptable to use experience sampling methods (ESM) among LGBTQ+ young people, who had current experiences of self-harm. Sixteen LGBTQ+ young people (16-25 years old) took part in the experience sampling study. This included a baseline assessment, a 7-day ESM assessment (participants were sampled 6 times a day using a phone app), and the option of an interview at the end of the 7-day ESM assessment. Feasibility data was descriptively analysed, with pilot ESM data presented. Qualitative data was thematically analysed to determine the acceptability (barriers and facilitators) of taking part in this study. Study feasibility was assessed by enrolment rate (55.2%), participant retention across assessment period (100%), ESM app feasibility (87.5%), and good adherence to total number of ESM surveys (67.6%). Individual study adherence ranged between 43-95.2%. Study acceptability was assessed by participant interviews. Thematic analysis indicated 4 superordinate themes; i) Self-reflection and awareness; ii) Practicalities of ESM surveys; iii) Daily timeframes; and iv) Suggestions for future studies. Pilot ESM data demonstrates that there was fluctuation of depressive and anxiety symptoms within- and between- participants over the course of the study, however greater sample power is needed for full analysis. This study demonstrated that ESM designs are feasible and acceptable among LGBTQ+ young people with current experiences of self-harm. Pilot data indicated that specific experiences and emotions are likely to be important to self-harm. These potentially have a temporal influence on self-harm behaviour or ideation, and therefore should be examined in a fully powered sample.